2019
DOI: 10.1016/j.bbrc.2018.12.111
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress is induced in growth plate hypertrophic chondrocytes in G610C mouse model of osteogenesis imperfecta

Abstract: Osteogenesis imperfecta (OI) is a hereditary bone disorder most commonly caused by autosomal dominant mutations in genes encoding type I collagen. In addition to bone fragility, patients suffer from impaired longitudinal bone growth. It has been demonstrated that in OI, an accumulation of mutated type I collagen in the endoplasmic reticulum (ER) induces ER stress in osteoblasts, causing osteoblast dysfunction leading to bone fragility. We hypothesize that ER stress is also induced in the growth plate where bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 28 publications
5
47
1
Order By: Relevance
“…Similarly, the G610C mice showed accelerated differentiation via increased hypertrophic zones. This is also reflective of a recently published study showing increased growth plate hypertrophic zones in G610C that are a result of defects in the maturation of hypertrophic chondrocytes . Therefore, it is possible that the increased cartilage content we see in the 1‐week G610C callus is a result of chondrocytes remaining hypertrophic for an extended period of time.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similarly, the G610C mice showed accelerated differentiation via increased hypertrophic zones. This is also reflective of a recently published study showing increased growth plate hypertrophic zones in G610C that are a result of defects in the maturation of hypertrophic chondrocytes . Therefore, it is possible that the increased cartilage content we see in the 1‐week G610C callus is a result of chondrocytes remaining hypertrophic for an extended period of time.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, although G610C mice also showed a reduced proportion of immature cartilage, they showed no change in proliferative cartilage and a trending increase in hypertrophic cartilage proportion at 1 week post‐fracture. G610C growth plates have been previously shown to have increased hypertrophic zones due to suppressed maturation . This indicates that G610C callus cartilage also exhibits accelerated chondrocyte maturation that may be stalled at the hypertrophic stage, translating to a depletion of available chondrocytes but an increase in cartilage proportion.…”
Section: Resultsmentioning
confidence: 99%
“…Because chondrocytes are characterized by the expression of fibrillar collagen type II and, upon becoming hypertrophic, of collagen type X, it is not clear how the alterations in type I collagen that cause OI negatively impact the biology and activity of these cells. However, Scheiber et al (45) showed recently that murine hypertrophic chondrocytes also express type I collagen and that, in the Col1a2 G610C/+ mouse model of OI, these cells in addition to osteoblasts had an abnormally large ER, which likely caused ER stress and a chondrocyte maturation defect. They also observed elongated growth plates, which translated into significantly shorter long bones (45).…”
Section: Short Staturementioning
confidence: 99%
“…However, Scheiber et al (45) showed recently that murine hypertrophic chondrocytes also express type I collagen and that, in the Col1a2 G610C/+ mouse model of OI, these cells in addition to osteoblasts had an abnormally large ER, which likely caused ER stress and a chondrocyte maturation defect. They also observed elongated growth plates, which translated into significantly shorter long bones (45). Therefore, at least in this mouse model of OI, dysfunctional hypertrophic chondrocytes contribute to short stature.…”
Section: Short Staturementioning
confidence: 99%
“…In spite of the lack of evidence proving direct link between ER stress presented in IBD and bone disease, the promising effect of UPR in bone cells differentiation and functions has been investigated in multiple studies. Scheiber et al showed that G610C osteogenesis imperfecta mice had longitudinal bone growth retardation, characterized by accumulated hypertrophic chondrocytes expressing ER dilation, and mutated type I collagen which induce osteoblast dysfunction due to ER stress [170]. ER stress also reflects one of the promising therapeutic mechanisms during rheumatoid disease process.…”
Section: Intestinal Barrier-regulated Bone Lossmentioning
confidence: 99%